Конструктивно-продукційне моделювання тривимірних фрактальних поверхонь - Шинкаренко, Віктор Іванович; Чигір, Роберт Романович (Український державний університет науки і технологій, ННІ ≪Дніпровський металургійний інститут≫, ІВК ≪Системні технології≫, Дніпро, 2025)
UKR: Представлено модель та програмне забезпечення для конструктивного моделювання фрактальних тривимірних поверхонь. Розроблено програмний додаток для попередньої підготовки поверхонь. Моделювання виконується на основі конструктивно-продукційного підходу. Основні процеси конструктивно-продукційного моделювання з застосуванням розроблених програмних засобів продемонстровано на прикладі моделей китайських пагод. Використано різні види конструкторів, розроблено мультикон-структор формування тривимірних фрактальних фігур на основі мультисимвольних граматик.

ENG: The study considers the fractal properties of architectural structures, in particular, multi-tiered structures such as a pagoda. The pagoda is an example of a building where each level repeats the geometric motif of the previous one, decreasing in scale but maintaining the overall structure and proportions. Representation of the pagoda model using fractal geometry and Bézier surfaces to reproduce curved elements is the main element of the work. An algorithm for the formation of an architectural structure, where each level is modelled on the basis of the previous one through a sequential reduction of its geometric elements, is proposed. The formation is carried out with the help of constructors based on constructive-synthesizing modelling. This approach allows for the automatic creation of new levels of the structure while maintaining their self-similarity. One of the key tools used in the work is parametric constructors, which allow generating three-dimensional images of multi-level structures. Particular attention is paid to Bezier surfaces, which are used to build curved elements at each level of the pagoda, ensuring smooth transitions between surfaces. The algorithmic constructors allow you to interactively adjust the parameters of the structure by changing the number of levels, their proportions and geometric features. As a result, a set of algorithms and tools for building fractal structures has been presented that can be used both in architectural design and in modelling complex geometric shapes. The process of creating such models is described in detail through an iterative approach, where each level of the structure is the result of modifying the previous one according to clearly defined rules.
Constructive-Synthesizing Modelling of Three-Dimensional Fractal Surfaces
В. Шинкаренко: ORCID 0000-0001-8738-7225
Keywords: конструктивно-продукційне моделювання; фрактал; L-система; пагода; конструктор; формальні граматики; поверхні Безьє; програмне забезпечення; інформаційні технології; constructive-synthesizing modelling; fractal; L-system; pagoda; constructor; formal grammars; Bézier surfaces; software; information technology; КІТ; TECHNOLOGY::Information technology